The Role of the Arab oil to the achievement of Economic security in the Arab: The Role of the Arab oil to the achievement of Economic security in the Arab (Journal of the College of Education for Women, 2019)
Abstract:This research aims to the importance of oil in achieving economicsecurity in the Arab. Oil is not an ordinary subject and returns it significance tothe followings:1. The importance of skipping a source of energy.2. The importance of oil as raw material for petrochemical industry.3. The importance of the oil sector as an area of foreign investment4. The importance of oil in the marketing activities, transport, insuranceand various servicesIn addition to the importance of oil in general and the Arab oil hasadditional strategic advantages such as geographic location, And themagnitude of reserves and production of heavy investment costs are relativelysimple, And the ability to meet the emergency needs of the market quickly andat low cost.These features and benefits that are granted to the decision makers inthe Arab oil sense, power and ability to meet the emergency needs of themarket quickly and at low cost.